Expert teacher perceptions of two-way feedback interaction - Tan, F.D.H.; Whipp, P.R.; Gagné, Marylène; Van Quaquebeke, N. (PERGAMON-ELSEVIER SCIENCE LTD, 2020)
The importance and influence of feedback is well-established in the literature (Hattie, 2009). The purpose of feedback is to improve learning (Voerman, Meijer, Korthagen, & Simons, 2012) by reducing discrepancies (Hattie, 2007), closing gaps (Sadler, 2010), and improving one's knowledge, and skill acquisition (Moreno, 2004). However, there is disjuncture concerning the effectiveness of unilateral or one-way feedback. Unilateral feedback has been critiqued for its failure to productively engage, guide learning, and monitor performance (Price, Handley, & Millar, 2011; Sadler, 1989). Despite calls to focus feedback on student learning outcomes (Hattie, 2009; Voerman et al., 2012), a third of feedback interventions have reported a decrease in student performance (Kluger & DeNisi, 1996). Research informs that feedback that focuses on self instead of task inhibits learning (Kluger & DeNisi, 1996; Shute, 2008). On the other hand, feedback that focuses on self-regulation, task, and cognitive processing enhances learning (Hattie & Timperley, 2007; Shute, 2008). However, teachers are observed delivering one-way feedback, rather than facilitating learning (Blair & Ginty, 2013; Van den Berghe, Ros, & Beijaard, 2013), and appear ‘to close down opportunities for exploring student learning rather than opening them up’ (Torrance & Pryor, 1988, p. 621). That is, self-focussed unilateral feedbackthwarts the potential to promote learning (Burke, 2009).